Spatial variability of soil phosphorus of a low productivity Brachiaria brizantha pasture - Edemar Joaquim Corazza; Michel Brossard; Takashi MuraokaI; Maurício Antonio Coelho Filho (Scientia Agricola, 2003)
Studies on soil phosphorus (P) of low productivity cultivated pastures in Cerrado (Brazilian Savanna) areas and surveys on other possible problems related to P are scarce. The spatial variability of soil phosphorus content of a Rhodic Ferralsol was studied in a low productivity pasture of Brachiaria brizantha (BB) grown for 10 years, without fertilizer application, in an experimental area at Planaltina (GO), Brazil. Soil samplings were performed on a regular grid of 10 by 10 meters, with 98 sampling points before (between tussocks and under tussocks) and after the establishment of the experiment (after fertilizing). On the same grid, forage plants were collected and separated into fractions for N and P content analyses. Soil available phosphate was determined by the resin method (Pr) and complemented by the 32P isotopic exchange kinetics analysis. Descriptive statistical and geostatistical analyses were utilized to describe the spatial variability. The Pr content on soil samples under tussocks presented mean and median values 45% larger than in soil samples taken between tussocks. The higher variation is probably related to the greater concentration of BB roots, soil organic matter content and soil P recycled through the plants tussocks. The spatial variability of Pr in this soil was high especially after fertilizer application. This variable did not present spatial dependence for the regular 10 m sampling. The generated knowledge on P variability of soils under low productivity cultivated pastures revealed problems related to the sampling methodology traditionally utilized and to P application.